Memaknai Upacara Kematian dalam Bingkai Lokalitas Budaya Indonesia: Studi Kasus Tiga Cerpen Pilihan Kompas - Awla akbar Ilma; Puri Bakthawar (SULUK: Jurnal Bahasa, Sastra, dan Budaya, 2020)
Indonesian is a multicultural plural society. Therefore, almost every ethnic group in Indonesia has varied tradition and culture, especially in responding to the phenomenon of obsequies through unique ceremonies and symbols. The research aims to examine how people in several ethnic groups responded to the death event through traditional ceremonies represented by literary works, especially short stories in the 2014-2017 Kompas Selections. Samples to be used in this study are the short story "In the Body of the Tarra, in the Womb of the Tree" by Faisal Oddang in 2014, the short story "Linuwih Aroma Jarik Baru" by Anggun Prameswari in 2015, and the short story "Kasur Tanah" by Muna Masyari in 2017. Results research shows that the three short stories elevate and interpret the tradition of obsequies in Javanese, Madura, and Toraja cultures. In Javanese society, kawung batik is a symbol of man's separation from the natural world. In Madurese society, Sortana is a "gift" of human separation from the social environment. In Toraja society, the tradition of passiliran becomes a symbol of the reuniting of humans with nature as the original.